Learning-by-Doing as a Propagation Mechanism - Chang, Yongsung; Gomes, Joao F; Schorfheide, Frank (American Economic Review, 2002)
This paper suggests that skill accumulation through past work experience, or “learning-by-doing” (LBD), can provide an important propagation mechanism in a dynamic stochastic general-equilibrium model, as the current labor supply affects future productivity. Our econometric analysis uses a Bayesian approach to combine micro-level panel data with aggregate time series. Formal model evaluation shows that the introduction of the LBD mechanism improves the model's ability to fit the dynamics of aggregate output and hours.